Knowledge, attitude, and practice on sugar-sweetened beverages among undergraduate students: a systematic literature review - Shahadan, Siti Zuhaidah; Salman, Siti Nuranina; Mohamad Ismail, Mohamad Firdaus (Academic Inspired Network, 2025)
The consumption of sugar-sweetened beverages (SSBs) has become a significant global public health concern, particularly among university students. SSBs are associated with adverse health outcomes, including obesity, type 2 diabetes mellitus (T2DM), and cardiovascular diseases (CVD). Despite increased awareness of these risks, SSB consumption remains prevalent. Understanding the knowledge, attitudes, and practices (KAP) related to SSBs is crucial for designing effective interventions to reduce intake and mitigate health risks. This systematic literature review examines the KAP related to SSB consumption among university students. A comprehensive search of four databases (ProQuest, Scopus, ScienceDirect, PubMed) was conducted using the PICO framework. Relevant studies were selected through predefined criteria, yielding 45 articles for analysis. The review revealed varied levels of knowledge about SSBs among students, with high awareness in some populations not always translating into healthier practices. Taste preference, peer influence, and habitual consumption emerged as dominant factors driving SSB intake. Attitudes generally reflected an understanding of SSB-associated health risks; however, practices such as frequent and high-quantity consumption persisted, highlighting a disconnect between knowledge and behaviour. The findings emphasise the need for targeted interventions to address the knowledge-behaviour gap in SSB consumption among university students. Public health campaigns, policy measures, and educational programs tailored to sociocultural contexts are essential to mitigate excessive SSB intake and its health implications.